Progressive Law in Indonesian Tax Legislation Reform: Balancing Tax Orientation and Substantive Justice - Bambang Sujatmiko; Zainal Arifin Hoesein (Universitas Ibn Khaldun, 2025)
This study examines the legal orientation of Indonesian tax legislation, which has historically emphasized the budgetary function of taxation as the primary instrument of state revenue. Using doctrinal and normative legal analysis, combined with qualitative methods, the study finds that this revenue-centric orientation tends to marginalize the substantive justice dimension of taxpayers' rights, reducing taxation to a bureaucratic obligation rather than a moral and constitutional relationship between citizens and the state. The qualitative component consists of semi-structured interviews with tax officials, legal practitioners, and taxpayer advocates, along with a purposeful analysis of parliamentary debates, ministerial policy papers, and selected court decisions, to capture how fiscal imperatives shape drafting choices, administrative practices, and taxpayer experiences. Drawing on Satjipto Rahardjo's progressive legal philosophy and Eugen Ehrlich's sociological jurisprudence, along with John Rawls's principles of justice and Amartya Sen's capabilities approach, this paper argues for a paradigm shift in tax law reform. The study proposes the integration of progressive legal principles that prioritize human welfare, contextual justice, and the protection of vulnerable groups, while maintaining legal certainty and administrative feasibility. The study concludes that aligning fiscal certainty with distributive justice requires rights-sensitive legal processes, transparent and participatory rulemaking, reasonable proportionality in sanctions and audits, and fairness-oriented design of exemptions, credits, and procedures. By reframing taxation as an instrument of social justice rather than simply a fiscal mechanism, future Indonesian tax legislation can enhance legitimacy, strengthen voluntary compliance, and realize constitutional commitments to equity and public welfare in a sustainable and context-sensitive manner at the national level. Keywords: Tax Law; Fiscal Justice; Progressive Legal Theory; Legal Reform; Substantive Justice